UPAYA PENINGKATAN KUALITAS AIR PRODUKSI PADA PERUSAHAAN XYZ KABUPATEN SRAGEN DENGAN METODE SIX SIGMA - Puspitasari, Finatiyani Mei; Handayani, Naniek Utami (Industrial Engineering Online Journal, 2024)
UPAYA PENINGKATAN KUALITAS AIR PRODUKSI PADA PERUSAHAANXYZ KABUPATEN SRAGEN DENGAN METODE SIX SIGMA Finatiyani Mei Puspitasari1), Naniek Utami Handayani2 *) *) Corresponding author email : finatiyani@students.undip.ac.id 1)Departemen Teknik Industri, Fakultas Teknik, Universitas Diponegoro2) Departemen Teknik Industri, Fakultas Teknik, Universitas Diponegoro  Article infoMODUL vol 2x no y, issues period 202xDoi AbstractQuality control is a process carried out with the aim ofensuring that the production output meets the specifiedquality standards. Perusahaan XYZ is a servicecompany engaged in water distribution, in which thereare issues with the quality of the production water. Someof the production water still does not meet the qualitystandards. Based on calculations, a Defects Per MillionOpportunities (DPMO) value of 2.465.277,7778 with aprocess sigma value of 2.1855 was obtained. Thepurpose of this study is to improve the quality of theproduction water. This quality improvement is carriedout using the six sigma method with the Define,Measure, Analyze, Improve concept. The tools used inthis study are Pareto diagrams, u-control charts,fishbone diagrams, and recommendations forimprovements are made using the Failure Mode andEffect Analysis (FMEA) method on the highest RPNvalue.Keywords: six sigma; quality control; FMEA; PDAM